Seed germination of common and endangered arable weed species is differently affected by the herbicide metazachlor and its transformation products - Garcia, Andrés; Eichberg, Carsten; Wendell, Anne-Kathrin; Pfeifer, Simon; Ludewig, Kristin; Donath, Tobias W.; Ulrich, Uta (Wiley, 2023)
High inputs of herbicides have caused the decline of arable weed species, which formerly evolved under less intensively managed crop lands. Arable weed species have adapted their germination strategies to respond to unfavourable periods. However, species considered endangered have more specific germination requirements. The herbicide metazachlor (MZ), in its formulated form Butisan®, is used for the control of annual and dicotyledonous weeds and degrades in the soil into two major transformation products (TPs): metazachlor oxalic acid (MZ-OA) and metazachlor ethane sulphonic acid (MZ-ESA). These TPs are often found in higher concentrations compared to MZ. We tested the effect of MZ and its TP on seed germination of four common and three endangered arable weed species present in Central Europe by setting up multi-factorial climate chamber experimental designs. We chose concentrations imitating field conditions and according to previously reported fraction occurrences in the topsoil. We assessed germination by measuring germination percentage, mean germination time and synchrony of germination. All germination variables were affected with increasing concentrations of MZ. Both, common and endangered species showed a decrease in germination percentage under the highest concentration of MZ. MZ and MZ-OA increased the synchronicity of endangered species, while both TPs decreased mean germination time of endangered species. Common species showed less significant differences when compared to the control and also had a less synchronised and longer germination time compared to endangered species. The observed response of common species to both MZ and TPs may be convenient in the face of short term unfavourable environmental conditions, such as those found in intensively managed arable lands. Our results highlight that the species-specific response of arable weeds to herbicides will further increase the dominance of common over rare arable weed species.